2021
DOI: 10.3389/fcell.2021.687099
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β Signaling Regulates Tooth Root Dentinogenesis by Cooperation With Wnt Signaling

Abstract: Proper differentiation of odontoblasts is crucial for the development of tooth roots. Previous studies have reported the osteogenic/odontogenic potential of pre-odontoblasts during root odontoblast differentiation. However, the underlying molecular pathway that orchestrates these processes remains largely unclear. In this study, ablation of transforming growth factor-β receptor type 2 (Tgfbr2) in root pre-odontoblasts resulted in abnormal formation of root osteodentin, which was associated with ectopic osteoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Of these, the Wnt signaling pathway ( Figure 7 ) was of particular interest due to its critical role in tooth development and odontoblast function ( Lohi et al, 2010 ), with Axin2 and Wnt10a significantly downregulated in MMP13KO samples, both of which have previously been highlighted to be reduced in the odontoblasts of malformed crowns in Wnt-less mice ( Bae et al, 2015 ). Wnt10a expression has been shown to induce DSP expression and odontoblast differentiation ( Yamashiro et al, 2007 ), while Axin2 expression in odontoblasts has been shown to enhance reparative dentinogenesis ( Babb et al, 2017 ) and root thickness ( Zhang et al, 2021 ) and has implicated Wnt/β-catenin signaling in odontoblast development and maturation ( Lohi et al, 2010 ; Babb et al, 2017 ). Axin2 is a direct target of canonical Wnt signaling ( Kim and Simmer 2007 ) and is seen in a restricted pattern during mouse embryogenesis and organogenesis with reports suggesting that Axin2 participates in a negative feedback loop that limits the duration of a Wnt-initiated signal ( Jho et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, the Wnt signaling pathway ( Figure 7 ) was of particular interest due to its critical role in tooth development and odontoblast function ( Lohi et al, 2010 ), with Axin2 and Wnt10a significantly downregulated in MMP13KO samples, both of which have previously been highlighted to be reduced in the odontoblasts of malformed crowns in Wnt-less mice ( Bae et al, 2015 ). Wnt10a expression has been shown to induce DSP expression and odontoblast differentiation ( Yamashiro et al, 2007 ), while Axin2 expression in odontoblasts has been shown to enhance reparative dentinogenesis ( Babb et al, 2017 ) and root thickness ( Zhang et al, 2021 ) and has implicated Wnt/β-catenin signaling in odontoblast development and maturation ( Lohi et al, 2010 ; Babb et al, 2017 ). Axin2 is a direct target of canonical Wnt signaling ( Kim and Simmer 2007 ) and is seen in a restricted pattern during mouse embryogenesis and organogenesis with reports suggesting that Axin2 participates in a negative feedback loop that limits the duration of a Wnt-initiated signal ( Jho et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Animal models with the deletion of transforming growth factor- β receptor type 2 in bone-producing mesenchyme led to an alteration in osteoblast organization [ 48 ]. Similarly, the deletion of transforming growth factor- β receptor type 2 in odontoblastic precursor cells resulted in the abnormal development of osteodentin [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 16 KEGG _ PATHWAY was enriched to 96 genes, and oas01100 (Metabolic pathways) were mainly enriched to 48 speci c genes. Genes WNT6, WNT10A, LEF1 and TCF7L1 were enriched in oas04310 (Wnt signaling pathway), oas04916 (Melanogenesis), oas05217 (Basal cell carcinoma pathway).The expression of WNT6 and WNT10A can stimulate the formation and differentiation of osteoblasts and play an important role in maintaining bone homeostasis [31] .Meanwhile, bone differentiation can promote the formation of the Generation of Osteocalcin and regulate tooth formation [52] . On the other hand, WNT signaling promotes the proliferation of melanocyte stem cells and drives their differentiation to produce pigment [53] .…”
Section: Exploring the Regulatory Mechanisms Of High-altitude Adaptiv...mentioning
confidence: 99%